Randomized trial of total fundoplication and fundal mobilization with or without division of short gastric vessels: a short-term clinical evaluation - Farah,José Francisco de Mattos (2007)
PURPOSE: Evaluate short results after fundoplication procedure, concerning the division of short gastric vessels. METHODS: A prospective randomization of 90 patients with indication for hiatoplasty and total fundoplication with fundus mobilization was performed. They were divided into two groups: no SGV division (group A, n= 46) and with SGV division (Group B, n=44), although in both groups the gastric fundus was mobilized to perform a floppy valve. Early outcome with clinical follow up (1 year) was observed. RESULTS: Both groups were similar regarding preoperative parameters and severity of gastroesophageal reflux disease (GERD). No difference in morbidity was observed during hospital stay. Nevertheless, the median operating time was 80,2 minutes in group A and 94,1 minutes (p=0,021) in Group B. Transitory dysphagia during the first year was significantly lower in group B (46,6% versus 23,2%, p=0,012). However, in 12 months clinical outcome was similar in both groups (clinical symptoms of GERD, persistent dysphagia and reoperations). CONCLUSION: There was no improvement in routine division of SGV in total fundoplication procedure when the gastric fundus was mobilized.